2014
DOI: 10.5644/ama2006-124.100
|View full text |Cite
|
Sign up to set email alerts
|

Teaching science throughout the six-year medical curriculum: Two-year experience from the University of Split School of Medicine, Split, Croatia

Abstract: Objective. e aim of this article is to present the introduction of a mandatory, vertically integrated course in research methodology into medical curriculum. At the School of Medicine in Split (Croatia) we organized this course in 2010, with the total of 270 hours in the 6-year curriculum. In the rst year (50 hours) students learned basic principles of scienti c method, structure of scienti c article, basic statistical concepts, data analysis, interpretation and presentation. In the second year (25 hours) stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…Presenting scientific results (N = 10) and student research projects (N = 10) were also part of publications identified in this review. Teaching interventions varied lengthwise, from three hours of workshop (24) to full-grown vertically integrated study programs (25)(26)(27)(28).…”
Section: Resultsmentioning
confidence: 99%
“…Presenting scientific results (N = 10) and student research projects (N = 10) were also part of publications identified in this review. Teaching interventions varied lengthwise, from three hours of workshop (24) to full-grown vertically integrated study programs (25)(26)(27)(28).…”
Section: Resultsmentioning
confidence: 99%
“…The requests for curricular changes issued by the European Commission were answered by shaping the Split curricula into an original blend of traditional pre-clinical and clinical subjects with several vertically integrated subjects focusing on mastering clinical skills, professional attitudes, information management and critical, as well as evidence-based reasoning and decision making (17). Marušić et al have found that the new course succeeded in increasing students' knowledge and skills for critical thinking and EBM, and prepared them for life-long learning in medicine (18).…”
Section: Cochrane Croatia: Involving Physicians Medical Students Andmentioning
confidence: 99%
“…Medical education at the tertiary level has been in existence since 1979 in Split, initially as a branch of the University of Zagreb School of Medicine and since 1997, as an independent School of Medicine within the University of Split (1). Establishing and developing new medical school is a long, laborious and expensive process, requiring not only infrastructural prerequisites, but also highly motivated and educated human resources.…”
Section: Introductionmentioning
confidence: 99%